Improved Blood Pressure Control to Reduce Cardiovascular Disease Morbidity and Mortality: The Standardized Hypertension Treatment and Prevention Project. Issue 12 (4th July 2016) - Patel, Pragna; Ordunez, Pedro; DiPette, Donald; Escobar, Maria Cristina; Hassell, Trevor; Wyss, Fernando; Hennis, Anselm; Asma, Samira; Angell, Sonia
Abstract : Hypertension is the leading remediable risk factor for cardiovascular disease, affecting more than 1 billion people worldwide, and is responsible for more than 10 million preventable deaths globally each year. While hypertension can be successfully diagnosed and treated, only one in seven persons with hypertension have controlled blood pressure. To meet the challenge of improving the control of hypertension, particularly in low‐ and middle‐income countries, the authors developed the Standardized Hypertension Treatment and Prevention Project, which involves a health systems–strengthening approach that advocates for standardized hypertension management using evidence‐based interventions. These interventions include the use of standardized treatment protocols, a core set of medications along with improved procurement mechanisms to increase the availability and affordability of these medications, registries for cohort monitoring and evaluation, patient empowerment, team‐based care (task shifting), and community engagement. With political will and strong partnerships, this approach provides the groundwork to reduce high blood pressure and cardiovascular disease‐related morbidity and mortality.